2021
DOI: 10.1111/gcb.15970
|View full text |Cite
|
Sign up to set email alerts
|

Coupling plant litter quantity to a novel metric for litter quality explains C storage changes in a thawing permafrost peatland

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…For example, through field, lab, and mechanistic modeling, thermodynamic properties of OM have been shown to influence microbial respiration in both aerobic and anaerobic river corridor settings (Boye et al, 2017;Graham et al, 2018;Garayburu-Caruso et al, 2020a;Song et al, 2020;Sengupta et al, 2021). This has also recently been shown in soil systems as well (Hough et al, 2022). Other attributes of OM chemistry, such as the carbon-to-nitrogen ratio, also have strong influences over river corridor rates and fluxes (Bauer et al, 2013;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…For example, through field, lab, and mechanistic modeling, thermodynamic properties of OM have been shown to influence microbial respiration in both aerobic and anaerobic river corridor settings (Boye et al, 2017;Graham et al, 2018;Garayburu-Caruso et al, 2020a;Song et al, 2020;Sengupta et al, 2021). This has also recently been shown in soil systems as well (Hough et al, 2022). Other attributes of OM chemistry, such as the carbon-to-nitrogen ratio, also have strong influences over river corridor rates and fluxes (Bauer et al, 2013;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…5). We observed habitat-and depth-specific metabolite and gene expression patterns, probably due to differences in plant and microbial community species between habitats 5,31 . Importantly, unlike PO alone (Fig.…”
Section: Articlementioning
confidence: 87%
“…It is commonly reported that litter decomposition responds to climate warming and its underlying mechanisms when litter is located on the soil surface (Hough et al, 2022;Yang et al, 2022; Frontiers in Ecology and Evolution 08 frontiersin.org . However, this is not always the case.…”
Section: Discussionmentioning
confidence: 99%